Hemispherically asymmetric trade wind changes as signatures of past ITCZ shifts. (15th January 2018) - McGee, David; Moreno-Chamarro, Eduardo; Green, Brian; Marshall, John; Galbraith, Eric; Bradtmiller, Louisa
Abstract: The atmospheric Hadley cells, which meet at the Intertropical Convergence Zone (ITCZ), play critical roles in transporting heat, driving ocean circulation and supplying precipitation to the most heavily populated regions of the globe. Paleo-reconstructions can provide concrete evidence of how these major features of the atmospheric circulation can change in response to climate perturbations. While most such reconstructions have focused on ITCZ-related rainfall, here we show that trade wind proxies can document dynamical aspects of meridional ITCZ shifts. Theoretical expectations based on angular momentum constraints and results from freshwater hosing simulations with two different climate models predict that ITCZ shifts due to anomalous cooling of one hemisphere would be accompanied by a strengthening of the Hadley cell and trade winds in the colder hemisphere, with an opposite response in the warmer hemisphere. This expectation of hemispherically asymmetric trade wind changes is confirmed by proxy data of coastal upwelling and windblown dust from the Atlantic basin during Heinrich stadials, showing trade wind strengthening in the Northern Hemisphere and weakening in the Southern Hemisphere subtropics in concert with southward ITCZ shifts. Data from other basins show broadly similar patterns, though improved constraints on past trade wind changes are needed outside the Atlantic Basin. The asymmetric trade wind changes identified here suggest that ITCZ shifts are also marked by intensification of the ocean's wind-driven subtropical cells in the cooler hemisphere and a weakening in the warmer hemisphere, which induces cross-equatorial oceanic heat transport into the colder hemisphere. This response would be expected to prevent extreme meridional ITCZ shifts in response to asymmetric heating or cooling. Understanding trade wind changes and their coupling to cross-equatorial ocean cells is key to better constraining ITCZ shifts and ocean and atmosphere dynamical changes in the past, especially for regions and time periods for which few paleodata exist, and also improves our understanding of what changes may occur in the future. Highlights: In ITCZ shifts, trade winds strengthen in cooler hemisphere, weaken in warmer. Asymmetric trade wind responses during ITCZ shifts predicted by theory and models. Proxy data show stronger NH trades, weaker SH trades during Heinrich stadials. Trade wind changes drive heat transport into the NH by ocean subtropical cells. Trade wind proxies trace dynamics of Hadley cell and ocean response during stadials.